Nursing students' perceptions of peer learning through cross‐cultural student‐led webinars: A qualitative study. (28th March 2019) - Carlson, Elisabeth; Stenberg, Marie; Lai, Timothy; Reisenhofer, Sonia; Chan, Bessie; Cruz, Eric; Leung, Doris; Wong, Arkers; Chan, Engle Angela
Abstract: Aims: To explore nursing students' perception of peer learning during cross‐cultural learning activities through student‐led webinars. Design: An exploratory qualitative study. Methods: Thematic analysis of data collected from reflective journals and focus‐group interviews of participating nursing students across three international universities in Australia, Hong Kong, and Sweden during autumn 2017. Results: Three themes were identified: peer learning as creation of friendship; peer learning from interactions that went beyond what was originally intended; and peer learning as empowered learning . Conclusion: Combining peer learning as an educational approach with cross‐cultural and student‐led webinars provided new perspectives. On‐line learning across global boundaries, based on a sound educational model, creates new opportunities for internationalization without straining individual and institutional financial resources. 摘要: 目的: 在跨文化学习活动中, 通过学生主导的在线研讨会探究护理专业学生对同伴学习的看法。 设计: 采用考察性定性研究。 方法: 本研究于2017年秋季通过反馈性日志以及焦点团体访谈收集数据, 其中由澳大利亚、香港和瑞典三个国际大学护理专业学生参与焦点团体访谈。 结果: 有三个主题:同伴学习建立友谊;同伴学习交流超过了原先的预想;同伴学习是能力的学习。 结论: 同伴学习作为一种教育方法, 同跨文化以及学生主导的在线研讨会相结合, 为教育提供了新的研究视角。基于完善的教育模式, 跨越国界进行在线学习, 为国际化创造了新的机遇, 不再受个人和机构资金资源的限制。